PERILAKU PEMBERIAN MAKAN ORANGTUA PREDIKTOR NEGATIF DENGAN KEJADIAN STUNTING ANAK USIA 24-59 BULAN - Dewi Maghfirotun; Prastiwi Putri Basuki; Yuli Ernawati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Poor nutritional condition is one of the causes of stunting. Parental feeding behavior plays a role inimproving children's nutritional status. The purpose of this research was to discover the correlationbetween parental feeding behavior and the incident of stunting among children aged 24-59 monthsat Sidoluhur Village Working Area of the Godean 1 Sleman Community Health Center. The researchmethods used an observational analytic design with a cross-sectional study. The respondents haveconducted 72 parents with children aged 24-59 months who fit the inclusion and exclusion criteria.Parental feeding behavior was assessed using the Parental Feeding Behavior Questionnaire whichconsists of 38 questions. The incidence of stunting was assessed by height indicator according toage (height/aged) were compared with z-score. Data were analyzed using Sommer’s d correlation.The result of the study indicates that parental feeding behavior is not associated with the incidenceof stunted (p = 0,639; r = -0,073). The average of parental feeding behavior mostly with sufficientcategory (59,7%). The incidence of stunting showed that 1 child (1,4%) with stunting and 8children (11,1%) with severe stunting.